Incidence and risk factors of post-extubation dysphagia in non-neurological critically ill patients - Marcotti Fernández, Anthony.; Manríquez Martínez, Daniela.; Guajardo Cuenca, Sebastián Alejandro.; Sandoval León, Karina. (Universidad de Castilla la Mancha, 2024)
Post-extubation dysphagia (PED) is a common complication in patients undergoing orotracheal intubation (OTI). Currently, there is significant heterogeneity in the reported incidence, ranging from 3% to 81%. Consensus on its risk factors is also lacking. This study aimed to determine the incidence and risk factors for PED in non-neurological adult patients. A retrospective longitudinal study was conducted by reviewing clinical records of patients who underwent OTI in a public hospital in Chile between June 2018 and June 2019. Cumulative incidence was estimated, and univariate and multivariate logistic regression models were used to identify risk factors. The presence/absence of PED was considered the response variable, with age, gender, days of OTI, assessment time, and admission diagnosis to the intensive care unit (ICU) as predictor variables. Data from 141 patients, comprising 72 males and 69 females, with an average age of 59 years, were collected. Of the patients, 73,05% presented with PED, and both age and days of OTI were identified as risk factors for PED. Gender, time elapsed until assessment, and the cause of admission to the ICU were not associated with the presence of PED. During the study period, a PED incidence of 73,05% was observed. The primary risk factor for PED was the duration of OTI, followed by age. The remaining variables studied did not demonstrate an association with the risk of PED.
Incidencia y factores de riesgo de disfagia post extubación en pacientes críticos no neurológicos
Keywords: Airway extubation; Cuidados críticos; Trastornos de deglución; Factores de riesgo